MyopicMAC: A Throughput-Optimal Random Access Scheme for Distributed Wireless Networks - Dinis, Rui (2018)
This work presents a novel Medium Access Control (MAC) algorithm for single-hop distributed wireless networks, MyopicMAC, which is designed to maximize the network throughput performance. In our scheme, all nodes adopt a common optimal contention window avoiding message passing, which is obtained through the use of the common view of the channel. MyopicMAC is also designed to improve the medium access fairness. This goal is achieved by adopting a contention window similar for all nodes. Departing from the optimal throughput for a saturated network, we devise a scheme to estimate the number of nodes, which is a prime parameter to regulate the medium access control. It is shown that each node is able to estimate the number of competing nodes by using both its own medium access probability and the idle slot probability observed in the channel. Several simulation results evaluate the throughput, fairness and delay performance obtained with our proposal. The possibility of transmission errors is also taken into account. A comparison is made with several state-of-the-art MAC algorithms, different number of competing nodes and different behaviors expressed by different transmission error probabilities. The obtained results indicate that MyopicMAC performs closer to the optimal throughput and simultaneously exhibit high medium access fairness. Moreover, because MyopicMAC does not take the success of previous transmissions in the contention regulation, the performance of the MAC algorithm is not affected by transmission errors.